Porous silicon carbide coated with tantalum as potential material for bone implants - Ma, Zhijie (Regen Biomater, 2020)
Porous silicon carbide (SiC) has a specific biomorphous microstructure similar to the trabecular microstructure of human bone. Compared with that of bioactive ceramics, such as calcium phosphate, SiC does not induce spontaneous interface bonding to living bone. In this study, bioactive tantalum (Ta) metal deposited on porous SiC scaffolds by chemical vapour deposition was investigated to accelerate osseointegration and improve the bonding to bones. Scanning electron microscopy indicated that the Ta coating evenly covered the entire scaffold structure. Energy-dispersive spectroscopy and X-ray diffraction analysis showed that the coating consisted of Ta phases. The bonding strength between the Ta coating and the SiC substrate is 88.4 MPa. The yield strength of porous SiC with a Ta coating (pTa) was 45.8 ± 2.9 MPa, the compressive strength was 61.4 ± 3.2 MPa and the elastic modulus was ∼4.8 GPa. When MG-63 human osteoblasts were co-cultured with pTa, osteoblasts showed good adhesion and spreading on the surface of the pTa and its porous structure, which showed that it has excellent bioactivity and cyto-compatibility. To further study the osseointegration properties of pTa. PTa and porous titanium (pTi) were implanted into the femoral neck of goats for 12 weeks, respectively. The Van-Gieson staining of histological sections results that the pTa group had better osseointegration than the pTi group. These results indicate that coating bioactive Ta metal on porous SiC scaffolds could be a potential material for bone substitutes.